# Solve for r -10rs+6r=7s

-10rs+6r=7s
Factor 2r out of -10rs+6r.
Factor 2r out of -10rs.
2r(-5s)+6r=7s
Factor 2r out of 6r.
2r(-5s)+2r(3)=7s
Factor 2r out of 2r(-5s)+2r(3).
2r(-5s+3)=7s
2r(-5s+3)=7s
Divide each term by 2(-5s+3) and simplify.
Divide each term in 2r(-5s+3)=7s by 2(-5s+3).
2r(-5s+3)2(-5s+3)=7s2(-5s+3)
Simplify 2r(-5s+3)2(-5s+3).
Cancel the common factor of 2.
Cancel the common factor.
2r(-5s+3)2(-5s+3)=7s2(-5s+3)
Rewrite the expression.
r(-5s+3)-5s+3=7s2(-5s+3)
r(-5s+3)-5s+3=7s2(-5s+3)
Cancel the common factor of -5s+3.
Cancel the common factor.
r(-5s+3)-5s+3=7s2(-5s+3)
Divide r by 1.
r=7s2(-5s+3)
r=7s2(-5s+3)
r=7s2(-5s+3)
Simplify 7s2(-5s+3).
Factor -1 out of -5s.
r=7s2(-(5s)+3)
Rewrite 3 as -1(-3).
r=7s2(-(5s)-1(-3))
Factor -1 out of -(5s)-1(-3).
r=7s2(-(5s-3))
Rewrite negatives.
Rewrite -(5s-3) as -1(5s-3).
r=7s2(-1(5s-3))
Move the negative in front of the fraction.
r=-7s2(5s-3)
r=-7s2(5s-3)
r=-7s2(5s-3)
r=-7s2(5s-3)
Solve for r -10rs+6r=7s

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top